2000
DOI: 10.1002/1097-0134(20001201)41:4<475::aid-prot50>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Covariance analysis of protein families: The case of the variable domains of antibodies

Abstract: A nonrestrictive method for identifying covariance in protein families is described and applied to human and mouse germline Vκ and VH sequence alignments. Amino acids that occur at each position in a sequence alignment are divided into two sets, called a word, by generating all possible combinations of alternative amino acids. Each word is associated with a pattern of changes. Words with identical patterns identify covariant positions. In antibody variable domains, the number of words generated ranged between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Despite an enormous amount of research involving antibodies and antibody‐like therapeutics, very little use has been made of covariation analyses to investigate functional features of antibody domains. A study by Altschuh and coworkers59, 60 investigated covariations across murine and human germline V H or V L sequences, with the goal of defining positions within each germline subclass that use mutually exclusive framework amino acid pairs to influence the structural conformations of CDR loops. Our study had a different goal: to use covariation analyses for determining naturally occurring amino acid networks, in antibody variable domains, that are generally important for antibody structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an enormous amount of research involving antibodies and antibody‐like therapeutics, very little use has been made of covariation analyses to investigate functional features of antibody domains. A study by Altschuh and coworkers59, 60 investigated covariations across murine and human germline V H or V L sequences, with the goal of defining positions within each germline subclass that use mutually exclusive framework amino acid pairs to influence the structural conformations of CDR loops. Our study had a different goal: to use covariation analyses for determining naturally occurring amino acid networks, in antibody variable domains, that are generally important for antibody structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…These couplings in sequence alignments have been studied for very different purposes, often with a link to protein structure, function and evolution [21][26]. In variable domains (Fv) of antibodies such cooperative mutations are found as well [27], [28]. But although a functional driving force for some correlated positions can not be excluded for antibodies, most of the correlated mutations in antibodies appear through different underlying germline genes and, although the cooperativity is statistically significant, a structural or functional cause seems unlikely for most of them, which is underscored by the fact that correlations in human sequences differ from correlations in murine sequences.…”
Section: Introductionmentioning
confidence: 99%
“…We are searching for protein engineering rules, applicable to at least a subgroup of antibodies, and have selected for mutagenesis residues located within the structurally conserved framework region, rather than in the highly variable complementarity determining regions (CDRs) that determine antigen‐binding specificity. The residues in question are co‐variant positions that were identified in an analysis of antibody germline sequence alignments (Choulier et al 2000): Two positions are co‐variant if the nature of amino acids at position A is not independent of the nature of amino acids at position B, indicating the existence of functional constraints linking these two residues (Altschuh et al 1987). The study by Choulier et al (2000) indicated the existence of a co‐variance signal for framework positions located at the surface of the variable region.…”
mentioning
confidence: 99%
“…The residues in question are co‐variant positions that were identified in an analysis of antibody germline sequence alignments (Choulier et al 2000): Two positions are co‐variant if the nature of amino acids at position A is not independent of the nature of amino acids at position B, indicating the existence of functional constraints linking these two residues (Altschuh et al 1987). The study by Choulier et al (2000) indicated the existence of a co‐variance signal for framework positions located at the surface of the variable region. In particular, for two co‐variant pairs identified in mouse antibody germline sequences (L18‐L74, H46‐H62, Kabat numbering), alternative amino acid types presented large differences in solvation free energy (Table 1), and the two positions of each pair were spatially close in the three‐dimensional structure of antibodies (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation